Effect of novel sequential soaking treatments on Maillard reaction products in potato and alternative vegetable crisps. Issue 7 (July 2021) - Ledbetter, Moira; Blidi, Slim; Ackon, Stefania; Bruno, Francesca; Sturrock, Keith; Pellegrini, Nicoletta; Fiore, Alberto
Abstract: Frying leads to the formation of numerous food contaminants through the Maillard reaction (MR). In this paper, commercially available vegetable crisps were analysed for and established to have high levels of acrylamide. Consequentially, the capability of two novel sequential pre-frying treatments were applied to potato, beetroot and parsnip snacks to inhibit the formation of acrylamide, 5-hydroxymethylfurfural (HMF), glyoxal (GO) and methylglyoxal (MGO) was investigated. Data revealed that immersion in cold tap water for 2 min followed by blanching at 70 ± 2 °C for 2 min (Cold soak, hot soak, (CSHS)) as well as soaking in a 0.01M CaCl2 solution for 2 min followed by blanching at 70 ± 2 °C in 0.1M citric acid for 2 min were both effective pre-treatments for potato crisps, simultaneously decreasing acrylamide concentration under the benchmark level of 750 μg/kg and lowering GO content by 55.19 and 54.67% and MGO concentration by 39.17% and 81.62%, respectively. CSHS was the only efficient treatment for concurrent mitigation of acrylamide (-41.64%) and HMF (-88.43%) with little GO and MGO development in beetroot. Sequential cold soak in 0.01M calcium chloride and hot soak in a 0.1M citric acid solution has been effective in decreasing acrylamide in alternative crisps. However, this led to an increase in HMF, 30 and 20-fold respectively from the initial concentration. Data reveal that the tested mitigation strategies are vegetable specific. Highlights: Vegetable crisps contain more acrylamide than the benchmark for potato crisps. Vegetable crisps contain significant levels of HMF, GO and MGO than potato crisps. Wash additives effect on potato, are variable on vegetable. Mitigation strategies for the reduction of acrylamide are vegetable specific. Abstract : Acrylamide, 5-hydroxymethylfurfural, glyoxal, methylglyoxal, vegetable crisps